The The Effect of Mental Disturbance Knowledge and Work Motivation on the Perception of Family Social Support and its Impact on the Performance of the Mental Health Cadres - Wahyu Sriharini; Nurdina Nurdina (Journal for Quality in Public Health, 2021)
Monitoring and evaluation survey data for the last three years shows motivation, perceptions of family social support and knowledge of mental disorders by Mental Health Cadres (MHCs) are still lacking . This will have an impact on the low performance of the MHCs duties. This study aims to analyze the effect of knowledge of mental disorders, work motivation and perceptions of social support from the family of People With Mental Disorders (PWMD) on the performance of MHCs, as well as mediating perceptions of social support for PWMD families on the influence of knowledge of mental disorders and work motivation on performance of MHC. The research subjects were 202 MHCs in Jombang Regency. Researcher developed the self-reports to measure of performance, work motivation and perceptions of family social support, as well as a mental disorder knowledge test. Research variable data were analyzed by path regression analysis. The results of the analysis show that knowledge of mental disorders, work motivation and perceptions of social support for PWMD families have a positive effect on performance of MHCs; The perception of social support from PWMD families does not mediate the effect of knowledge of mental disorders and work motivation on performance of MHCs. The research findings will be discussed in the context of the MHCs.